Microprocessor Architecture , Programming & Applications 8085 - Gaokar R. (Mumbai Penram Publishing, 2013)
About the Book: Microprocessor Architecture, Programming and Applications with the 8085 This book provides a comprehensive treatment of the microprocessor, covering both hardware and software based on the 8085 Microprocessor family. This book was first published in 1984 and it has been in the field for nearly three decades. The microprocessor concepts that were at the cutting edge of the technology in the 1970s and 80s have become fundamentals of the computer field. It is gratifying to see such acceptance of the integrated approach to teaching microprocessor concepts.